Valores organizacionales y actitudes de identificación con la gestión de calidad del servicio nacional de adiestramiento en trabajo industrial la libertad: propuesta de modelo de capacitación empresarial con perspectiva antropológica - Moreno Gonzáles, Gladys (2007)
In this work a diagnosis of the organizational culture of the National Service of Training in Industrial Employment (SENATI), La Libertad, on the basis of the changes from the last five years 2000-2005 is proposed. The research design was descriptive-observational of the face transversal. Among the results it has to remark: 1) the presence of organizational values of results (client satisfaction) of quality process by 68% in of the workers, 2) the Attitudes of no identification with the model of Quality Management, in the Satisfaction factor, whose non favorable attitudes reach 56.59%, followed by the Leadership factor with a 45.27%, which is considered a cultural feature of labor insatisfaction and insufficient connection between the predominant organizational culture and the Quality Culture in which it develops, 3) The preferred desired culture is the Culture of Performance (119) similar to the Culture of Support which had desired level of a 109. These results reveal a decreasing tendency in the predominance of organizational cultures of Power (84.5) and Function (63) found, an increase of the preference for the cultures of Performance (0.73) and the of Support (0.72) for the future being observed. The proposal is a Model of Enterprise training from an Anthropological perspective, an strategy of organizational learning, whose contents are designed according to the structure of learning, cognitive, affective and behavior area, and incorporates psycho-educational techniques.